Traverser la ville ininterrompue : sentir et se figurer à l’aveugle. À propos de Walk, Hands, Eyes (a city) de Myriam Lefkowitz - Julie Perrin (Ambiances)
In Walk, Hands, Eyes (a city), choreographer Myriam Lefkowitz invites a spectator to walk in an urban environment, in silence and with eyes closed. This article looks at the spatial, imaginary, sensory and kinaesthetic dimensions of the artistic experience, to question the way sensory knowledge specific to contemporary dance leads people to wander in and consider a city differently.